Optimalisasi Daya Saing Profesional Siswa SMA St. Louis 2 Surabaya melalui Professional Lifeskills Training - Eric Sulindra; Yohanes Adven Sarbani; Anastasia Nelladia Cendra; Andreas Emmanuel Hadisoebroto; Indriana Lestari; Caeciliai Setya Budi Wahyun; Gesti Memarista; Deatri Arumsari Agung (ISAS (Indonesian Society of Applied Science), 2025)
In today’s era of globalization, digital transformation, and increasingly competitive job markets, high school (SMA) and vocational school (SMK) students are expected to excel not only in academics but also in essential life skills. Abilities such as managing digital information and communicating professionally are now critical assets for building a career and achieving independence. Unfortunately, many graduates still face a gap between the skills they have and what the professional world requires. For instance, they often lack proficiency in productive digital tools like Microsoft Excel and have little awareness of the importance of developing a personal digital brand through platforms such as LinkedIn or professional email. To address this gap, the Professional Life Skills Training program was introduced as a strategic initiative to help SMAK St. Louis 2 students grow holistically and strengthen their future competitiveness. This training goes beyond teaching technical skills; it also fosters the mindset and attitudes needed to thrive in the 21st-century workplace.